EMBRACING CALMNESS THROUGH THE AISLE OF NATURE: A PROBE INTO CHITRA BANERJEE DIVAKARUNI’S THE FOREST OF ENCHANTMENTS. (International Journal of Food and Nutritional Sciences, 2022)
Human life is inexorably connected with nature and this connection has been celebrated by various traditions throughout ages. With the rapid growth of technology and industries, the sacred bond between humans and nature has gone interred under the layers of modernity and materialism. Creative artists use art as a tool to wrap the populace with the quilt of awareness about the need to shield the environment. In the sphere of literature Chitra Banerjee Divakaruni serves as a torch bearer who throws light on the various issues that munch the growth of the society. In her novel, The Forest of Enchantments along with many issues she elegantly touches upon the unfathomable role of nature in the wellbeing of human community. This article aims to delineate the benevolent kernel of nature that guides the populace towards the pinnacle of peace.